2019
DOI: 10.19094/contextus.v17i2.41214
|View full text |Cite
|
Sign up to set email alerts
|

Produção Científica Em Relações De Trabalho E Gestão De Pessoas (2000/2017)

Abstract: As conexões entre Relações de Trabalho (RT) e Gestão de Pessoas (GP) são inevitáveis, visto que ambas envolvem interações em contexto de trabalho. Este estudo objetivou mapear a produção científica das áreas, dos anos 2000 a 2017, dos artigos indexados na base de dados Web of Science (WoS). A partir de análise bibliométrica quantitativa-descritiva, examinou-se o comportamento da literatura nacional e internacional em relação a sua distribuição temporal, por idioma e por periódicos, bem como frequência de autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
1
0
5
Order By: Relevance
“…We conducted a systematic literature review aiming at summarizing and analyzing what has been published regarding production management applications in the context of dental service provision. This study reproduces Hofmann and Bosshard's (2017) research method, also following suggestions and methods found in Gil (2010), Rousseau, Manning, and Denyer (2008), Nery et al (2018), Grupo Prisma (2015), and Gemelli, Fraga, and Prestes (2019).…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…We conducted a systematic literature review aiming at summarizing and analyzing what has been published regarding production management applications in the context of dental service provision. This study reproduces Hofmann and Bosshard's (2017) research method, also following suggestions and methods found in Gil (2010), Rousseau, Manning, and Denyer (2008), Nery et al (2018), Grupo Prisma (2015), and Gemelli, Fraga, and Prestes (2019).…”
Section: Methodssupporting
confidence: 81%
“…Each researcher examined separately, autonomously, and independently the 17 selected papers and organized them into distinct variables in a Microsoft Excel spreadsheet, going up to 20 variables for analysis and extraction of contents that were pertinent to the research topic, such as main results, methodological characteristics, settings where the studies were conducted and suggestions for future research. To have a bibliometric view, the papers' titles, abstracts and keywords were used to create a word cloud (GEMELLI et al, 2019) that shows the main terms related to the topic.…”
Section: Results Organization and Classificationmentioning
confidence: 99%
“…54372/pc.2024.v19.3461 competitiva nas organizações (Coura et al, 2020;Demo et al, 2018;Motta, Vasconcelos, 2006;Legge, 2005;Mathis, Jackson, 2003). Já no campo de Relações de Trabalho, Gemelli et al (2019) afirmam que, embora a área de relações de trabalho tenha a mesma origem que a de gestão de pessoas, elas possuem distinções e parecem seguir caminhos diferentes, principalmente no Brasil. A área de relações de trabalho possui uma perspectiva de análise macro e externa, voltada ao entendimento das relações entre os atores sociais coletivos.…”
Section: Fundamentação Teóricaunclassified
“…Pesquisas que sistematizam a produção de um campo científico são relevantes por permitirem mapear o conhecimento já produzido e traçar perspectivas para discussões futuras (GEMELLI; FRAGA; PRESTES, 2019). Estudos nacionais anteriores realizaram esforços de sistematização e/ou análise das publicações científicas sobre a docência no Ensino Superior, demonstrando o amplo potencial de contribuição dessa categoria de trabalhos para os campos teórico e empírico acerca dessa temática.…”
Section: Introductionunclassified